1999
DOI: 10.1111/j.1559-1816.1999.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Proenvironmental Intention and Behavior by Personal Norms and the Theory of Planned Behavior1

Abstract: The value of personal norms (Schwartz, 1977) for proenvironmental behavior has been demonstrated in previous studies (e.g., Vining & Ebreo, 1992), but not in addition to the theory of planned behavior (Ajzen & Madden, 1986). In the present study, this combination was investigated by means of a mail survey among a sample of 305 Dutch citizens who were enlisted to participate in a behavioral change intervention program on environmentally relevant behavior. Personal norms appear to increase the proportion of expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
521
3
17

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 749 publications
(612 citation statements)
references
References 51 publications
38
521
3
17
Order By: Relevance
“…Our equivocal results plus the conflicting findings in other work (e.g. Harland et al, 1999;Kaiser & Scheuthle, 2003) suggest that the jury is still out on the added value of MO. When alternative career intention was not included in the analyses, MO accounted for significant amounts of variance in intention for the unqualified and in-training groups, but not for the qualified.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our equivocal results plus the conflicting findings in other work (e.g. Harland et al, 1999;Kaiser & Scheuthle, 2003) suggest that the jury is still out on the added value of MO. When alternative career intention was not included in the analyses, MO accounted for significant amounts of variance in intention for the unqualified and in-training groups, but not for the qualified.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies have found that MO adds to the prediction of intention and/or behavior over and above the core TPB variables (e.g. Parker, Manstead & Stradling, 1995;Harland, Staats & Wilke, 1999). However, in a large-scale longitudinal study, MO was not found to add significantly to the explanation of recycling behavior over and above the core TPB variables (Kaiser & Scheuthle, 2003).…”
Section: Introductionmentioning
confidence: 79%
“…Evidence was found as far back as 1999 that personal norms were a determinant in pro-environmental behavior, including using means of transport other that the car (Harland et al, 1999). More recent research into environmental awareness and attitudes suggests that a moral norm to take action to help the environment is important in forming intentions to make travel behaviour changes which reduce carbon emissions.…”
Section: Datamentioning
confidence: 99%
“…Similarly, Abrahamse et al (2009) reported that intentions to reduce car use were "mostly explained by ... personal norms". These moral norms can be assessed through measurement of perceived responsibility (Eriksson et al, 2008) and moral obligation (Harland et al, 1999;Abrahamse et al, 2009) to take action to be environmentally friendly, and perceived responsibility and moral obligation to travel by…”
Section: Datamentioning
confidence: 99%
“…PNBs are incorporated in our model in order to capture the influence of personal reasoning on tourists' decision making for selecting a destination. As researchers note, PNBs illuminate the importance of self-evaluative personal standards or goals associated with an ideal-self in shaping one's formation of intention and behavior (Abraham, Sheeran & Johnston, 1998;Bandura, 1998;Harland, Staats & Wilke, 1999, 2007Miniard and Cohen, 1983;Triandis, 1977).…”
Section: Introductionmentioning
confidence: 99%